Melamine related urinary calculus and acute renal failure in infants - Sun, Ning (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2008)
OBJECTIVE: To summarize clinical characteristics, diagnosis and treatment of infants with urinary calculus and acute renal failure developed after being fed with melamine tainted formula milk